Morbidity Pattern Among Children Aged 3 to 6 Years Residing in an Urban Slum: A Cross-Sectional Study (GAIMS Journal of Medical Sciences, 2026)
Background: Children residing in urban slums face a wide range of health problems such as malnutrition, respiratory infections, and gastrointestinal problems. These health problems are driven by factors like poor sanitation, polluted water, limited access to the health care services, lack of proper nutrition and environmental hazards. These issues contribute to poor physical and cognitive development and increased morbidity among the children. The objective of this study was to observe the morbidity and its socio-demographic determinants among slum children.Material and Methods: This cross-sectional study was conducted among children residing in an urban slum in Thane in January 2025 using complete enumeration technique. All the children aged 3 to 6 years residing in a defined urban slum were included in the study. Thorough clinical examination of the subjects was performed through house-to-house survey. Socio-demographic data and clinical examination findings were recorded in the proforma. Data was entered in Microsoft excel and statistically analyzed. Chi-square test was applied.Results: Total 159 children were examined. 51.57% were females and 48.43% were males. 59.12% subjects had morbidity. Respiratory problems were the most frequent (44.03%). Morbidity did not show any statistically significant association with gender, age, religion, or class. It was slightly higher among males (59.74%), and among children aged 3-4 years (61.82%). Also, it was higher among Hindu children (64.29%). Across classes, morbidity was most common in Junior Kindergarten (71.43%), followed by Nursery (52.83%) and Senior Kindergarten (52.00%) (p>0.05).Conclusion: Understanding and addressing children’s health in slum settings should be a priority for the health care services.